2006
DOI: 10.1038/nm1389
|View full text |Cite
|
Sign up to set email alerts
|

Thymus-derived leukemia-lymphoma in mice transgenic for the Tax gene of human T-lymphotropic virus type I

Abstract: Adult T-cell leukemia-lymphoma (ATLL) is a group of T-cell malignancies caused by infection with human T-lymphotropic virus type I (HTLV-I). Although the pathogenesis of ATLL remains incompletely understood, the viral regulatory protein Tax is centrally involved in cellular transformation. Here we describe the generation of HTLV-I Tax transgenic mice using the Lck proximal promoter to restrict transgene expression to developing thymocytes. After prolonged latency periods, transgenic mice developed diffuse larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
231
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(238 citation statements)
references
References 25 publications
5
231
0
2
Order By: Relevance
“…Extant findings have shown that Tax is sufficient to transform human T cells [10,11]. Hence, the expression of Tax-alone in transgenic mice was found to be fully proficient for in vivo tumorigenesis [12][13][14]. Indeed, current data are consistent with the notion that Tax expression in infected humans greatly accelerates the in vivo cycling of T cells [15].…”
supporting
confidence: 76%
“…Extant findings have shown that Tax is sufficient to transform human T cells [10,11]. Hence, the expression of Tax-alone in transgenic mice was found to be fully proficient for in vivo tumorigenesis [12][13][14]. Indeed, current data are consistent with the notion that Tax expression in infected humans greatly accelerates the in vivo cycling of T cells [15].…”
supporting
confidence: 76%
“…However, transgenic expression of Tax in the thymus induced immature T-cell lymphomas (36). These findings suggest that overexpression of Tax is oncogenic even for thymocytes, but that Tax expression or functions are normally impaired in the thymus of infected individuals.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, as exemplified with the E2A-deficient mice, the expression of Tax, by inactivating E2A proteins in immature thymocytes, might be followed by the emergence of a malignant lymphoproliferation. Thus, transgenic mice, in which Tax is expressed under the control of the Lck proximal promoter (which restricts transgene expression to developing thymocytes), after a long latency period develop lymphoma and leukemia with constitutive activation of NF-B (20). As a matter of fact, activation of this pathway is one of the main features of ATL cells, in which Tax expression is not or is rarely detected (14,17).…”
Section: Discussionmentioning
confidence: 99%